2016
DOI: 10.1186/s12889-016-3483-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of occupational injuries among municipal solid waste collectors in four zones of Amhara region, Northwest Ethiopia

Abstract: BackgroundRefuse collectors are at a high risk for fatal and non-fatal occupational accidents. This is more intensified in developing countries, like Ethiopia, due to physically demanding nature of the job. However, information on occupational injuries and related factors are almost non-existent in Ethiopia. Thus, the aim of this study was to assess the prevalence of occupational injuries and its associated factors.MethodsA cross-sectional study was conducted among municipal solid waste collectors in four zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
63
5
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 20 publications
14
63
5
10
Order By: Relevance
“…In this study majority of respondents (60%) have got work experience greater than 20 years and 92.4% have got salary more than NPR 18,500 which might have improved their job performance and chance of better treatment due to which 25.4% were found to be less exposed to work-related injury which was lower than other studies 34.3 % in Amara region of Northwest Ethiopia 13 and 43.7% in Addidas Ababa City 6 .…”
Section: Original Articlecontrasting
confidence: 49%
“…In this study majority of respondents (60%) have got work experience greater than 20 years and 92.4% have got salary more than NPR 18,500 which might have improved their job performance and chance of better treatment due to which 25.4% were found to be less exposed to work-related injury which was lower than other studies 34.3 % in Amara region of Northwest Ethiopia 13 and 43.7% in Addidas Ababa City 6 .…”
Section: Original Articlecontrasting
confidence: 49%
“…On the perception it was revealed that majority of the respondents under survey had a good knowledge of health risk and were fully aware of the environmental health risk associated with waste dumping and this correlates with the findings of Eskezia et al [11].…”
Section: Resultssupporting
confidence: 83%
“…Worldwide, there have been several studies on work accidents and safety and health risk management. In Paraguay, a study conducted by Flores, Carvalho e Radon (2018) concluded that each year about 37.5% of collecting workers suffer work accident; which is in accordance with the data published by the Canadian Union of Public Employees (CUPE, 2010) showing a percentage of 35%; and in accordance with the data from Ethiopia showing a percentage of 34.3% of collecting workers suffering accidents every year (Eskezia ET AL., 2016). The Bureau of Labor Statistics (BLS) from USA (United States of America, 2017) show similar results, stating that the activities of waste collection and maintenance are one the top five services which were responsible for most accidents, with the risk for waste collectors being 10 times higher compared with the mean value from all other sectors in the USA.…”
Section: Introductionsupporting
confidence: 68%